All Set Free: How God is Revealed in Jesus and Why That is Really Good News - Distefano, Matthew J. (Wipf and Stock Publishers, 2015)
What is the ending to the human drama? Will all be reconciled to God in the end? Does God demand an altar, a corpse, and blood? Or, rather, is the Christian God set apart from all the other gods throughout history?All Set Free sets out to answer some of the more difficult questions Christians today are faced with. It will challenge the Augustinian understanding of hell and the Calvinist understanding of the atonement; replacing them with a more Christ-centered understanding of both doctrines. This book will also use the work of Rene Girard in order to reshape how many understand "what it means to be human." Then and only then should we ask: "Who is God?" Come explore what has become Matthew's theological pilgrimage to this point. Come discover the God of peace